DINAMIKA PEMBAGIAN HARTA WARISAN PERSPEKTIF SYARIAT ISLAM DAN ADAT - Rahman, Rahman; Zulaiha, Habibah; Maulana, Ahmad Mu’is; S.Pd.I., M.Sy, Taupiq; Siregar, Sawaluddin (Yurisprudentia: Jurnal Hukum Ekonomi, 2024)
The people of Angkola Muaratais sub-district are predominantly Muslim and are identical in their customs, so when distributing inheritance, the community is done in a variety of ways, including how to determine the number of shares for each heir, the law used in dividing inheritance, determining who has the right. become the heir, the time and settlement carried out in the distribution of inherited assets. The research used is an empirical legal research method or what is known as socio-legal research, which only places law as a social phenomenon, thus, the law is viewed from the outside only which focuses on the behavior of individuals or society about the law, such as this research, namely Division Settlement. Inherited Assets in the Angkola Muaratais Community. The findings in this research are that there are three legal systems applied in the distribution of inherited assets, namely distribution by customary law, division by Islamic Law, and Civil Law (BW). The peaceful settlement of the distribution of inheritance among the community occurs because it contains goodness, by the principles of kinship and the values of justice adhered to by the local community. The factors that influence people to make peace before and after knowing their respective parts are social factors, cultural factors, educational, economic, and religious factors.